THE VALUE OF DIGITAL CHANGE IN COMBATING FINANCIAL FRAUD IN THE BANKING SECTOR - Khamroev, Sherzod Akhtamovich; Kholikova, Rukhsora Sanjarovna (INTERNATIONAL CONFERENCES, 2023)
Financial fraud is commonly used to describe an act of dishonesty involving financial transactions for personal gain. Hence, the next thesis will disclose the potential solutions provided by digital reform to avoid the problem.